2020
DOI: 10.3390/w12020322
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Conditions for Aerobic/Anaerobic Biodegradation of Chlorinated Ethenes—A Multi-Site Assessment

Abstract: A stall of cis-1,2-DCE and vinyl chloride (VC) is frequently observed during bioremediation of groundwater chloroethenes via reductive dechlorination. These chloroethenes may be oxidised by aerobic methanotrophs or ethenotrophs co-metabolically and/or metabolically. We assessed the potential for such oxidation at 12 sites (49 groundwater samples) using hydrochemical and molecular biological tools. Both ethenotroph (etnC and etnE) and methanotroph (mmoX and pmoA) functional genes were identified in 90% of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, detection of the ethenotroph functional gene etnE indicated the potential for ethenotroph-mediated aerobic biodegradation of CE metabolites. Co-occurrence of OHRB and VC assimilating bacteria has also been found in groundwater[17,52,53] and discrete aquifer soil samples[25] at other sites.…”
mentioning
confidence: 66%
“…Furthermore, detection of the ethenotroph functional gene etnE indicated the potential for ethenotroph-mediated aerobic biodegradation of CE metabolites. Co-occurrence of OHRB and VC assimilating bacteria has also been found in groundwater[17,52,53] and discrete aquifer soil samples[25] at other sites.…”
mentioning
confidence: 66%
“…The concentration of TCE was about 0.0 to 0.7μM, however, there was accumulation of cDCE and VC, the by-products of the degradation of PCE and TCE.The anaerobic simulated aquifer also saw a large amount of methane production (3.6 to 11.4 μM). Since the fermenters, methanogens, and dechlorination bacteria all competed for hydrogen at the same time (Patil et al, 2014;Ziv-El et al, 2012;Wen et al, 2015), the dechlorination ability of the dechlorination bacteria was reduced, so PCE could only be dechlorinated to cDCE and VC.Many studies have also shown that the anaerobic biodegradation of PCE usually results in the accumulation of cDCE and VC and is accompanied by the formation of a large amount of methane (Anam et al,2019;Major et al, 2002).Some studies have found that TCE, cDCE and VC can be cometabolically degraded by using methane as a substrate under aerobic conditions (Fogel et al, 1986;Němeček et al, 2020;Wymore et al, 2007). Therefore, this test inoculated acclimated methanotrophs in the following aerobic simulated aquifer, using methane generated in the anaerobic simulated aquifer as the carbon source and energy source of the methanotrophs, to produce methane monooxygenases.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular methods were the same as described Němeček et al (2020) [19], see Table 2. qPCR and the detection of the following functional microbial groups were observed: (i) sulfate-reducing bacteria-functional gene apsA; (ii) denitrifying bacteria-functional gene nirK; dechlorinating bacteria-16S rRNA gene specific for Dehalococcoides spp., Dehalobacter spp., Desulfitobacterium spp.…”
Section: Monitoringmentioning
confidence: 99%